2021
DOI: 10.3390/biology10040320
|View full text |Cite
|
Sign up to set email alerts
|

Growth Forms and Functional Guilds Distribution of Soil Fungi in Coastal Versus Inland Sites of Victoria Land, Antarctica

Abstract: In Victoria Land, Antarctica, ice-free areas are restricted to coastal regions and dominate the landscape of the McMurdo Dry Valleys. These two environments are subjected to different pressures that determine the establishment of highly adapted fungal communities. Within the kingdom of fungi, filamentous, yeasts and meristematic/microcolonial growth forms on one side and different lifestyles on the other side may be considered adaptive strategies of particular interest in the frame of Antarctic constraints. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…Basidiomycetous yeast Mrakia blollopis changed their morphology under different nutrient conditions [ 40 ]; M. blollopis showed yeast cells on eutrophic media and hyphal cells on oligotrophic media. Filamentous growth allows fungi to explore a more excellent surface search for water and nutrients and makes it possible to form aggregates to retain water and nutrients in unconsolidated and sandy soils [ 8 ]. On the other hand, G. antarctica kept the yeast-form under the conditions tested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Basidiomycetous yeast Mrakia blollopis changed their morphology under different nutrient conditions [ 40 ]; M. blollopis showed yeast cells on eutrophic media and hyphal cells on oligotrophic media. Filamentous growth allows fungi to explore a more excellent surface search for water and nutrients and makes it possible to form aggregates to retain water and nutrients in unconsolidated and sandy soils [ 8 ]. On the other hand, G. antarctica kept the yeast-form under the conditions tested.…”
Section: Resultsmentioning
confidence: 99%
“…Basidiomycetous yeasts have belonged in Pucciniomycotina , Ustilaginomycotina , and Tremellomycetes in Agricomycotina . Tremellomycetes and Agaricomycetes (known species were filamentous form) were detected in soils near glacial lakes in the McMurdo Dry Valley [ 7 ] and Victoria Land [ 8 ] by DNA metabarcording, and Tremellomycetes were the dominant taxa in these areas. DNA metabarcording suggested that Coprinellus and Pleurotus (both in Agaricomycetes) were included in dominant fungal taxa on rocks in the polar desert of the Ellsworth Mountains [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of seasonality and fine soil texture in shaping the soil microbial community was recently demonstrated at global scale (Delgado‐Baquerizo et al ., 2016). In addition, soil texture is an important predictor in promoting soil fungal richness globally (Xia et al ., 2020; Ding and Eldridge, 2020), which is consistent with the results of a recent study conducted on black yeasts from soils of Antarctic desert (Canini et al ., 2021). On the other hand, high levels of UV light are known to reduce the abundance of several fungal lineages (Pfendler et al ., 2019) as well as other microbial groups (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, for many species, their natural habitat is still unknown and hence their actual ecology remains enigmatic. Recent studies reported them also as fundamental inhabitants of Antarctic soils (Canini et al ., 2021). Despite their prominent contribution to key terrestrial processes, the proportion of black yeasts has been largely neglected in both regional, continental and global‐scale soil surveys (Maestre et al ., 2015; Cox et al ., 2016; Eldridge and Delgado‐Baquerizo, 2018; Egidi et al ., 2019; Větrovský et al ., 2019; Regmi and Huettmann, 2020).…”
Section: Introductionmentioning
confidence: 99%